If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 86 + -24x = -20x + -130 Reorder the terms: 86 + -24x = -130 + -20x Solving 86 + -24x = -130 + -20x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '20x' to each side of the equation. 86 + -24x + 20x = -130 + -20x + 20x Combine like terms: -24x + 20x = -4x 86 + -4x = -130 + -20x + 20x Combine like terms: -20x + 20x = 0 86 + -4x = -130 + 0 86 + -4x = -130 Add '-86' to each side of the equation. 86 + -86 + -4x = -130 + -86 Combine like terms: 86 + -86 = 0 0 + -4x = -130 + -86 -4x = -130 + -86 Combine like terms: -130 + -86 = -216 -4x = -216 Divide each side by '-4'. x = 54 Simplifying x = 54
| factor-3x^2-10x+8=0 | | 7.5(x-3)=0.5x+41.5 | | 2x-(10)=14 | | 8Z+12=5z,21 | | 22x+1160=15x+1900 | | 6x^2+6=-20 | | 4x-10=4y | | -7x+30=-12x+20 | | 3=39 | | -5y+4=7y-8 | | 4+z+2=2 | | 3x+6py-7=0 | | y-11=-10 | | (5p^3)(-m^8p^2)= | | -5x+17=-20x-18 | | p=s-14 | | 36x+200=76x | | x-11=5x | | 12x-4=96x-12 | | y=3x+-8 | | 4(x-y)(x-y)-25= | | 26x+9=8x+39 | | b+10=-13 | | 8=vu | | 3a-3=4a-1.5 | | x^2-18=19 | | (9-y)(4y+6)=0 | | 17+26x=30 | | -2x^2-x-3=0 | | 14-t=-10 | | 8.26x+4=68.2276+2x | | y=-.2x+12 |